A bibliometric analysis of socially responsible investment based on thematic clustering - Neenu Chalissery; Mosab I. Tabash; Mohamed Nishad T; Mamdouh Abdulaziz Saleh Al-Faryan (Cogent Business & Management, 2023)
Recently, scholarly interest in Socially Responsible Investment has increased significantly, and it is now regarded as one of the most important fields in business and strategy literature. The growth of socially conscious investors is a key component of the continuous quest for enhanced corporate social responsibility. The bibliometric analysis of 540 publications extracted from the Scopus database exhibits multi-folded growth in socially responsible investment literature from 1991 through 2021. The mapping of bibliographic data based on citation, co-authorship, and co-occurrence revealed the logical framework and connections among the contributing journals, countries, and articles. Further, the study used bibliographic coupling and statistical analysis such as factor analysis, correlation, and regression to evaluate the thematic cluster of documents and factors influencing the total citation of research articles. Even though the trend of publication in this field of research has been increasing over the years, most of the research on the topic was undertaken in developed countries like USA and U.K. The studies were few in the case of developing and emerging nations, especially in India. Developed countries concentrate more on sustainable practices. But it is equally important for develop-ing and emerging economies. The regression analysis disclosed that the length of the article (Ø = 0.42) and thematic clusters (Ø = 0.29, 0.46, and 0.44) have a sig-nificant positive relation with total citation. Most of the studies have concentrated on evaluating the socially responsible investment from the perspective of the corporate, investor, performance evaluation, and political, social, and environmental perspectives.
Keywords: 650; bibliometric analysis; correlation; ordinary least square regression; Socially responsible investment; thematic clustering